AlIII‐Catalysed Formation of Poly(limonene)carbonate: DFT Analysis of the Origin of Stereoregularity. Issue 16 (3rd March 2015) - Peña Carrodeguas, Leticia; González‐Fabra, Joan; Castro‐Gómez, Fernando; Bo, Carles; Kleij, Arjan W.
Abstract Amino‐triphenolate derived AlIII complexes combined with suitable nucleophiles have been investigated as binary catalysts for the coupling of limonene oxide and carbon dioxide to afford alternating polycarbonates. These catalysts are able to produce stereoregular, perfectly alternating trans‐polymers from cis‐limonene oxide, whereas the pure trans isomer and cis/trans mixture give rise to lower degrees of stereoregularity. The best AlIII catalyst shows the potential to mediate the conversion of both stereoisomers of limonene oxide with high conversion levels of up to 71 % under neat conditions, indicating the high degree of robustness and atom‐efficiency of this catalytic process. Computational studies have revealed unique features of the binary catalyst system, among which is the preferred nucleophilic attack on the quaternary carbon centre in the limonene oxide substrate.